(3TQM fgL GdHdGZIs - (3CHhMGeO YRGdOjf YHO GdMejO Hf gHI Gddg Hf eMeO Hf GdMSjfj Hf CHi GdMOjOs; (3GdTQja GdeQJVj , CHh GdbGSe,J (B436 (3g` s ((3Ydi Hf efUhQ Hf MSjf GdRjOi s)
(3ChdgG (B:s
(3hef cJGH dg Ydjg GdSdGe Edi Cgd GdHUQI(B: (3hbO cGf ef GfJTGQ NJdce hTbGbce s
(3BNQgG (B:s
(3hCf jUhf hLgi Yf GdeNdbjf, hjca Yfi YGOjI GdXGdejf Je GdcJGH s
(3cJHgG CcKQ ef fGSNs
(3hcJHJ HQSe QFjS GdeMOKjf GdTjN MSjf GdTYQis
(3fSNI QGHYIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs